Sexual structure of population and reproduction cycle of Lekanesphaera monodi (Arcangeli, 1934) (Crustacea, Isopoda) in the fouling community of the Odessa Bay, Black Sea - Варігін, О. Ю. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The sexual structure of population and specificities of reproduction cycle of Lekanesphaera monodi in the fouling community of the Odessa Bay, Black Sea have been studied. Annual changes of the sex ratio in the crustacean have been shown. The reproduction of L. monodi begins in late spring and ends in late autumn, but most intensively this process occurs in summer. The data on fertility of this species in the conditions of fouling community have been presented. The relationship of this parameter with length and weight of the crustacean have been shown. The equations of the dependence of wet and dry weights of males, oviparous and nonoviparous females of L. monodi on their length have been presented.